ANALISIS TINGKAT PENGETAHUAN KARYAWAN TERHADAP KEDISIPLINNAN PEMAKAIAN ALAT PELINDUNG DIRI DI PT XYZ - Simanjuntak, Gabariel; Arista, Anggia (Computer Science and Industrial Engineering, 2022)
PT XYZ is a company that provides Electronic Manufacturing Services (EMS) which focuses on design, engineering, and manufacturing services for automotive, industrial and computer. In the facility maintenance department, there is a work accident problem with data on the number of work accidents for the last one year period as many as 24 cases. The purpose of this study is to identify the factors that cause accidents in the workplace, determine the level of knowledge of employees regarding discipline regarding the use of personal protective equipment (PPE), and determine the level of knowledge of employees regarding the use of personal protective equipment (PPE). Finding a solution to improve your knowledge. The method used in this study is the Hazard and Operate Study (HAZOP) method. The number of samples surveyed this time was 30. Data collection consisted of questionnaires on each object to determine the characteristics of respondents, measurement of employees' level of knowledge in the area of ​​using personal protective equipment (PPE), and analysis of data on the Guttman scale. done by The results of this study show that there are still many undisciplined employees who do not know how to use personal protective equipment (PPE), which translates into an average employee knowledge level of 33%. concluded from the results. There is still an important relationship between employee knowledge and discipline when using PPE. Additional occupational health and safety training is recommended for each employee to increase employee knowledge and awareness of the importance of proper and correct use of personal protective equipment (PPE) in the workplace.